Genotyping of a family with a novel deleterious DPYD mutation supports the pretherapeutic screening of DPD deficiency with dihydrouracil/uracil ratio. Issue 2 (10th November 2015) - Thomas, F; Hennebelle, I; Delmas, C; Lochon, I; Dhelens, C; Garnier Tixidre, C; Bonadona, A; Penel, N; Goncalves, A; Delord, JP; Toulas, C; Chatelut, E
Abstract : Despite the growing evidence that dihydropyrimidine dehydrogenase deficiency (DPD, encoded by the DPYD gene) confers a higher risk of developing severe toxicity, most patients are not screened for DPD deficiency before fluoropyrimidine treatment. We report here the genetic and phenotypic analyses of DPD in a family related to a patient who died after a first cycle of 5‐fluorouracil and in 15 additional retrospective patients having a partial DPD deficiency (as measured by plasma dihydrouracil/uracil ratio). The patient with lethal toxicity was found to be a compound heterozygote for two DPYD mutations: a novel 8‐bp duplication (c.168_175dupGAATAATT, p.Phe59Ter) and c.1679T>G (Ile560Ser). The patient's dihydrouracil/uracil ratio indicates complete DPD deficiency. The novel mutation was found in two members of the patient's family. Deleterious DPYD mutations were identified in 9 out of the 15 patients. The relationship between genotype and dihydrouracil/uracil values in the 22 patients of the present study was significant ( P = 0.01) .